Holmes' reformulation through elements of feminist in Enola Holmes - Sampe, Marssy Diana (Aksara: Jurnal Bahasa dan Sastra, 2023)
As time goes by, fiction has become a medium that satisfies people’s wishes. This phenomenon happens because the purpose of popular fiction is to fulfill people's demands of plot lines. Therefore, the storyline or narrative of the story is a crucial point in discussing popular fiction. Genre becomes the key point in discussing the formulation of a story. This formulation is based on convention and one of the famous formulations is the genre of detective. One of the famous works of detectives is Sherlock Holmes. Holmes has created his own world and has produced so many adaptations. One of the adaptations that hooked people's attention is a spin-off work of Sherlock Holmes, Enola Holmes. Enola Holmes is a novel series written by Springer that got recognition from many people because she wrote a story on the line of Sherlock Holmes’s canonical story. Due to the fame, this series got adapted into film as Jack Thorne rewrote the story based on the original. However, Enola—written by Springer and Thorne—represents a contra point in the formulation. In order to discover and prove the formulation, this study focuses on using genre critcisim focusing on the formulation of feminist in the objects. Furthermore, this study also uses genre theories by Cawelti and Gelder in conducting the discussion. This research proves that Enola is a detective story by following the classical detective formula following the original formulation by Doyle on Sherlock. The problem of contra point is represented in the invention or innovation of the detective genre as it is taking women as the detective and main villain and a mystery around women characters.